Identification and quantification of phenanthrene ortho-quinones in human urine and their association with lipid peroxidation. (November 2020) - Luo, Kai; Carmella, Steven G.; Zhao, Yingchun; Tang, Mei Kuen; Hecht, Stephen S.
Abstract: Although human exposure to polycyclic aromatic hydrocarbons (PAH) has been associated with in vivo oxidative damage, and hydroxyPAH metabolites have been used as biomarkers to assess PAH-induced oxidative stress, few studies have looked at the likely causative compounds for oxidative stress in humans - PAH quinones. We developed a method using pre-column derivatization - liquid chromatography-heated electrospray ionization-tandem mass spectrometry (LC-HESI-MS/MS) to analyze ortho- phenanthrene quinones (PheQs) in human urine. 1, 2-PheQ and 3, 4-PheQ were identified and quantified in 3 mL of human urine; their total concentrations were higher in cigarette smokers (0.79 ± 0.98 nmol/6h urine) than in nonsmokers (0.20 ± 0.98 nmol/6h urine) ( p  < 0.01). The total of 1, 2-PheQ and 3, 4-PheQ were more strongly correlated with urinary ( Z )-7-[1 R, 2 R, 3 R, 5 S )-3, 5-dihydroxy-2-[( E, 3 S )-3-hydroxyoct-1-enyl]cyclopentyl]hept-5-enoic acid (8- iso -PGF2α ), a biomarker of lipid peroxidation (R 2  = 0.53, p  < 0.001), than the other phenanthrene metabolites including phenanthrene tetraol (PheT), phenanthrene-1, 2-dihydrodiol (1, 2-PheD), and total phenanthrene phenols (OHPhe), consistent with the concept that PheQs and likely other PAH quinones play a causal role in the generation of reactive oxygen species (ROS) in humans. Thus, PheQs may be suitable as biomarkers to assess human exposure to oxygenated PAH and the subsequent oxidative damage. This study provides unique support, by analysis of human urinary metabolites, for the PAH quinone mediated oxidative damage hypothesis of PAH carcinogenesis. Graphical abstract: Image 1 Highlights: Determination of Phe ortho -quinone isomers for the first time in human urine (N = 50). Urinary PheQ were significantly higher in cigarette smokers than non-smokers ( p  < 0.01). Strong positive correlation (R 2  = 0.53, p  < 0.001) between urinary PheQ and 8- iso -PGF2α . Urinary PheQ are suitable biomarker of exposure to oxy-PAH and oxidative damage. First human in vivo evidence supporting the hypothesis of PAH quinones carcinogenesis.